Deconstructing the Draft: An Evaluation of the NFL Draft as a Predictor of Team Success - Zachary Reynolds; Traci Bonds; Steele Thompson; Carrie W. LeCrom (Journal of Applied Sports Management, 2015)
The purpose of this investigation was to determine if the National Football League's (NFL) draft selection process aids in equalizing competitive advantage for NFL teams. This reverse order system (the draft) is said to equalize team strength by allowing weaker teams to strengthen their rosters with access to the best incoming players (Lock & Gratz, 1983). To measure this success, authors evaluated the correlation between a team's change in winning percentage and its Draft Pick Value (DPV), number of first-round picks, and total number of picks. Findings indicate a moderate positive correlation between DPV and change in winning percentage, and low positive correlations between change in winning percentage and number of first-round draft picks, and change in winning percentage and total number of picks.
Keywords: NFL draft; competitive advantage; draft pick value